Effect of dynamic cupping therapy vs. vibrating foam roller on pain, range of motion, function, and quality of life in elderly with subacute and chronic osteoarthritis of knee: A randomized controlled trial - Vijayalaxmi Kanabur; Anil R Muragod (MGM Journal of Medical Sciences, 2022)
Background: Knee osteoarthritis (KOA) is a frequent degenerative disease of joints. The prevalence is approximately 28% among the Indian elderly. Recently complementary and alternative medicine therapies have been used in managing pain and disability. Dynamic cupping therapy is one of the forms used nowadays. Foam rolling and vibration therapy is also a popular intervention in musculoskeletal conditions such as osteoarthritis, osteoporosis, sarcopenia, and low back pain. Nowadays, these two have been combined for the development of vibrating foam rollers. Objectives: This research aimed to compare the result of dynamic cupping therapy to that of a vibrating foam roller on pain, range of motion, function, and quality of life in elderly with sub-acute and chronic KOA. Materials and Methods: The research was carried out on 45 subjects with subacute to chronic KOA who were given thrice a week sessions for 4 weeks’ intervention. Through the randomized method, subjects were divided into a conventional group, dynamic cupping group and vibrating foam roller group outcome measures Numeric Pain Rating Scale, knee range of motion, Western Ontario and McMaster Universities Arthritis Index (WOMAC), and brief Older People′s Quality of Life Questionnaire (OPQOL-brief) were used. Results: Wilcoxon rank test revealed a pre-post difference in all three groups with significant P-values which were <0.05 and heterogeneously favored different outcome measures used. Kruskal–Wallis test revealed no difference between the groups. Conclusion: This study concluded that dynamic cupping therapy and vibration foam roller protocols used for the management of KOA are equally effective.